Peran Notaris Dalam Pelaksanaan Sistem Online Single Submission Terhadap Investasi Dengan Konsep Ease Of Doing Business - Utama, Made Yudi Sastra; Wisanjaya, I Gede Pasek Eka (Acta Comitas : Jurnal Hukum Kenotariatan, 2024)
The purpose of the research is to look at the implementation of the OSS system and examine the role of OSS in relation to PP No. 24 of 2018. The research method used is normative juridical using primary and secondary data and through literature study. Until now, the OSS policy has not been implemented optimally, this is due to obstacles in the integrated electronic system. However, the transparency of business licensing procedures and the ease of doing business are very visible through this OSS system. The role of a Notary in registering and managing business permits through OSS is based on statutory regulations. Notaries do not have the authority to carry out OSS, because in the OSS system it can be done by every business owner, but the Notary's authority to fill in integrated business permit data electronically is an acquired authority. through the granting of power of attorney by the business actor himself. The process of processing business entity permits after the implementation of the OSS means that business actors can have separate access in terms of registration, validation of business permits and of course reduces time and bureaucratic systems to support government efforts, namely easy access to business in Indonesia.